Nuclear receptors at the crossroads of inflammation and atherosclerosis - Glass, Christopher (Henry Stewart Talks, 2009)
Nuclear receptors comprise a superfamily of ligand- and signal-dependent transcription factors that regulate diverse aspects of reproduction, development, metabolism and immunity, Recent studies have demonstrated that a subset of nuclear receptors can co-ordinately regulate aspects of inflammation and metabolism that impact on the development of atherosclerosis and type 2 diabetes by inhibiting transcriptional responses to toll like receptors, The nuclear receptor co-repressor NCoR plays a key role in maintaining inflammatory response genes in a repressed state under basal conditions, PPARg inhibits inflammatory responses by preventing the removal of NCoR from target genes